Efficacy of Hip Strengthening Exercises Compared With Leg Strengthening Exercises on Knee Pain, Function, and Quality of Life in Patients With Knee Osteoarthritis. Issue 6 (November 2015) - Lun, Victor; Marsh, Andrew; Bray, Robert; Lindsay, David; Wiley, Preston
Abstract : Objective: The purpose of this study was to compare the efficacy of hip and leg strengthening exercise programs on knee pain, function, and quality of life (QOL) of patients with knee osteoarthritis (KOA). Design: Single-Blinded Randomized Clinical Trial. Setting: Patients with KOA. Participants: Male and female subjects were recruited from patients referred to the University of Calgary Sport Medicine Center and from newspaper advertisements. Interventions: Thirty-seven and 35 patients with KOA were randomly assigned to either a 12-week hip or leg strengthening exercise program, respectively. Both exercise programs consisted of strengthening and flexibility exercises, which were completed 3 to 5 days a week. The first 3 weeks of exercise were supervised and the remaining 9 weeks consisted of at-home exercise. Main Outcome Measures: Knee Injury and Osteoarthritis Score (KOOS) and Western Ontario McMaster Arthritis Index (WOMAC) questionnaires, 6-minute walk test, hip and knee range of motion (ROM), and hip and leg muscle strength. Results: Statistically and clinically significant improvements in the KOOS and WOMAC pain subscale scores were observed in both the hip and leg strengthening programs. There was no statistical difference in the change in scores observed between the 2 groups. Equal improvements in the KOOS and WOMAC function and QOL subscales were observed for both programs. There was no change in hip and knee ROM or hip and leg strength in either group. Conclusions: Isolated hip and leg strengthening exercise programs seem to similarly improve knee pain, function, and QOL in patients with KOA. Clinical Relevance: The results of this study show that both hip and leg strengthening exercises improve pain and QOL in patients with KOA and should be incorporated into the exercise prescription of patients with KOA. Abstract : Supplemental Digital Content is Available in the Text.